Long-Run Underperformance on Seasoned Equity Offerings: An Evidence from Indonesia - Abdur Rafik; Salsabila Annisa Azmi (Bina Nusantara University, 2019)
The research aimed to analyze the underperformance phenomenon following Seasoned Equity Offering (SEO)in Indonesian context. Samples were all firms listed on the Indonesia Stock Exchange with the right issue in the observed periods, were chosen by purposive sampling with several criteria. In total, there were 109 issuing firms from 2009-2014 that were analyzed using performance benchmarking approaches. The approaches consisted of market-based, size-based, growth-based, and industry-based benchmarks. The market-based was constructed using a market return. Then, the size and the growth benchmarks were constructed on the basis of closest market capitalization and closest price-to-book value respectively. Then, the industry benchmark was based on a closest combined of market capitalization and Price to Book Value (PBV) of matched firms within the first-second digit of Standard Industry Classification (SIC). The test was conducted using standard t and Wilcoxon tests by examining the benchmark-based abnormal returns over various spans ranging from 3 to 36 months following the right offerings. Like several findings in developed countries, the results also confirm the underperformance phenomenon following right offerings in Indonesia. The negative abnormal returns are found for all benchmark performances, but they are only significant for the market benchmark and partially significant for the size and the growth benchmarks. Behavioral explanations need to be modeled to reveal the intuitions behind the results.